2017
DOI: 10.1007/s11010-017-2963-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of JAK/STAT pathway restrains TSLP-activated dendritic cells mediated inflammatory T helper type 2 cell response in allergic rhinitis

Abstract: Thymic stromal lymphopoietin (TSLP) has recently been implicated as a key molecule for initiating allergic rhinitis (AR) at the cell-dendritic cell (DC) interface. Previous studies demonstrated that TSLP activated DCs to express more OX40 ligand (OX40L), which is associated with the initiation of T helper type 2 (Th2) cell responses. STAT phosphorylation has been reported to be promoted by TSLP. Thus, we investigated if the JAK/STAT pathway inhibitor CYT387 could affect TSLP-DC-mediated Th2 cell response in na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…Different STATs have been shown to be expressed during Mo-DC differentiation and maturation, with STAT1-3-5 and 6 phosphorylated during Mo-DC differentiation, and STAT1 and STAT3 being further activated during TLR maturation ( 61 ). Furthermore, the JAK1/2 inhibitor CYT387, has been shown repress DC differentiation and maturation, reducing their capacity to promote T cell differentiation ( 62 ), similarly the JAK2 inhibitor AG490 has also been shown to be involved in mediating DC maturation ( 63 ). In addition, our group has previously shown that the JAK/STAT pathway is one of the pathway involved in Mo-DC differentiation ( 8 ), and STAT3 inhibition has been shown to repress endothelial cells differentiation from DC ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different STATs have been shown to be expressed during Mo-DC differentiation and maturation, with STAT1-3-5 and 6 phosphorylated during Mo-DC differentiation, and STAT1 and STAT3 being further activated during TLR maturation ( 61 ). Furthermore, the JAK1/2 inhibitor CYT387, has been shown repress DC differentiation and maturation, reducing their capacity to promote T cell differentiation ( 62 ), similarly the JAK2 inhibitor AG490 has also been shown to be involved in mediating DC maturation ( 63 ). In addition, our group has previously shown that the JAK/STAT pathway is one of the pathway involved in Mo-DC differentiation ( 8 ), and STAT3 inhibition has been shown to repress endothelial cells differentiation from DC ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study supported our findings showing that the expression of OX40L was dramatically downregulated in TSLP-primed DCs by inhibiting the JAK/STAT pathway following CYT387 treatment in an asthmatic cell model. 11 In addition, the expression levels of the classic Th2 cytokines, namely IL-5 and IL-13 were markedly increased in the AC group. This alteration was diminished in the AC + miR-19b group and in the AC + CYT387 group.…”
Section: Discussionmentioning
confidence: 93%
“…9 In addition, TSLPR ligation has been found to phosphorylate STAT3 in human subjects. 10 Previous reports indicated that DC maturation was significantly inhibited by the JAK/STAT pathway inhibitor (CYT387) in allergic diseases 11 and that STAT3 was required for Th2 cell development and cytokine production following activation. 12 In the present study, we speculated that the JAK/STAT pathway in DCs was important in regulating AC downstream of TSLP.…”
mentioning
confidence: 99%
“…Serum total and OVA-specific IgE levels were significantly increased in OVA-stimulated mice. As an exogenous antigen, OVA stimulates B cells to produce IgE and activate mast cells [ 17 ]. Intranasal instillation of EOCO suppressed the serum OVA-specific IgE level, but did not influence the total serum IgE level.…”
Section: Discussionmentioning
confidence: 99%